Effective learning activity to facilitate post‐graduate nursing students' utilization of nursing theories – Using the fundamentals of care framework. (29th March 2022) - Jangland, Eva; Gunnarsson, Anna‐Karin; Hauffman, Anna; Edfeldt, Katarina; Nyholm, Lena; Fröjd, Camilla
Abstract: Aims: To explore how postgraduate nursing students used the Fundamentals of Care framework in a written assignment based on a clinical situation, and describe their learning process in using the framework. Design: A qualitative descriptive study design applying the Fundamentals of Care framework. Methods: Postgraduate nursing students' theoretical written assignments ( n  = 35) based on self‐experienced clinical cases were included. The data were collected in 2021 in five specialties in a postgraduate nursing programme in Sweden. The data were analysed using content analysis. Results: Applying the framework to a self‐experienced clinical case illuminated the importance of nurse–patient relationships and clarified the meaning of person‐centred care. The students assessed the framework as easy‐to‐use bedside as a guide to providing nursing care. By using the framework, the students were aided in reasoning about the fundamental values of care such as ethics, equality in healthcare and patient rights. When students reflected on their learning process, they stated that the assignment taught them how to use the framework, as well as paving the way for finding and applying other theories of nursing. Conclusion: Learning activities with an opportunity to practice analysing nursing care guided by a theory, combined with a self‐evaluating element, are conducive to deepening students' learning and improving their ability to use theories in clinical practice. Impact: The framework illuminated the importance of the nurse–patient relationship in nursing care to the students and made them recognize and value the clinical use of theories. It is the responsibility of leaders in nurse education and healthcare to provide the next generation of specialist nurses—future nursing leaders—with regular opportunities to analyse nursing care through theories and frameworks. Nurses call for continuous learning on theories; leaders in nurse education and healthcare must meet these needs.